On a Problem of Production Planning for a Non-Storable Commodity - Zaki, R. M.; Bhattacharyya, B. B.; Anderson, R. L. (Management Science, 1964)
This paper is concerned with the decision problem faced by a firm which produces a non-storable commodity and has to spend large amounts of capital on a specialized factor that could remain idle part of the time because of fluctuations in production. The optimum decision rule is derived under one resource restriction and an explicit parametric solution has been obtained. The model has then been extended to incorporate more than one resource restriction, for which certain parametric solutions have been obtained.